Comparison of Perioperative Outcomes Between Precise and Routine Segmentectomy for Patients With Early-Stage Lung Cancer Presenting as Ground-Glass Opacities: A Propensity Score-Matched Study - Wu, Xianning; Li, Tian; Zhang, Chuankai; Wu, Gao; Xiong, Ran; Xu, Meiqing; Su, Dan; Xie, Mingran (Frontiers in Oncology, 2021)
Introduction: Segmentectomy is widely used for early-stage lung cancer presenting as single or multiple ground-glass opacities (GGOs). Precise segmentectomy is the recommended procedure in China. However, clinically, most routine segmentectomies are performed using only high-resolution computed tomography (CT). The aim of this study was to evaluate the effect of two segmentectomy approaches for GGOs in the lung. Methods: From January 2020 to September 2020, 55 precise segmentectomies performed with real-time guidance using 3D reconstruction and 343 routine segmentectomies for patients with single or multiple GGOs were performedas uniportal procedures. To reduce bias related to outcomes, preoperative clinical factors were used for propensity score matching (1:1); 55 precision and 55 routine segmentectomies were selected and further analyzed. Perioperative outcomes, namely operation time, blood loss, resection margins, number of removed lymph nodes, postoperative pulmonary function (1 month after surgery), length of postoperative stay, and postoperative complications were compared between the two groups. Results: Patients constituted 43 men and 67 women, with an age range of 25–68 years (median: 53 years). No significant differences were seen between the groups regarding blood loss, complications, histological type, and postoperative pulmonary function, and there were no 30-day postoperative deaths in either group. The median operation time for the Precision group (74 minutes) was longer than in the Routine group (55 minutes) (p < 0.01), and the number of removed lymph nodes in the Precision group (5±1.1) was higher than in the Routine group(3±0.8)(p <0.01). Chest tube duration days and postoperative stay days were similar in both groups; however, the rate of air leakage on postoperative day 1 was higher in the Precision group(p =0.020). All patients in the Precision group had adequate resection margins. Four patients (7.3%) undergoing complex segmentectomy in the Routine group had inadequate resection margins and required resection of additional lung tissue. Conclusion: Routine segmentectomy can significantly shorten the operation time and might prevent postoperative air leakage in uniportal segmentectomy for lung GGOs. However, precision segmentectomy may be more precise for complex cases, ensuring adequate resection margins and lymph node dissection.